(3Gdbhd GdeCfhS HTQM eZdb GdbGehSs - (3HOQ GdOjf eMeO Hf jMji Hf YeQ GdbQGais
(3ChdgG (B:s
(3GdMeO ddg GdPi , CbGe eLO GdOjf hHYO , aEf Gddg SHMGfg TQa gPg GddZI Ydi SGFQ GddZGJ hbaJ Ydi HYV JbGjjO HWQ ai gPG GdcJGH HNW GdTjN YHO GdHGSW s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg (B: (3UQM HPdc GdSjhWi ai (B" (3GdeRgQ(B" (3Hd bGd (B: (3CYXe cJGH Cda ai GddZI HYO YUQ GdUMGM Ke cJGH GdbGehS ddEeGe eLO GdOjf GdajQhRGHGOi hSjCJi dgPG JJeI bGd s
(3GdeNWhW bWYI ef Chdg abWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B185 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs